1991
DOI: 10.1084/jem.173.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Human platelet-mediated cytotoxicity against Toxoplasma gondii: role of thromboxane.

Abstract: Human platelets, in the absence of antibody, are cytotoxic to tachyzoites of Toxoplasma gondii as determined by vital staining, transmission electron microscopy, and the failure of Toxoplasma to survive and replicate in mice after in vitro interaction of the organisms with platelets. Platelet to T. gondii ratios as low as 1:3 were toxic to the organisms with direct cell-cell contact essential for platelet-mediated cytotoxicity. Adherence of platelets to T. gondii and disruption of surface membranes and cytopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 46 publications
(64 reference statements)
5
40
0
Order By: Relevance
“…3). T. gondii incubated in buffer alone for 90 min release PGE2 (73.4 pg per 106 organisms in 90 min as we have previously reported [21]) but do not generate mono-HETEs or 5-1ipoxygenase products.…”
Section: Resultsmentioning
confidence: 72%
See 3 more Smart Citations
“…3). T. gondii incubated in buffer alone for 90 min release PGE2 (73.4 pg per 106 organisms in 90 min as we have previously reported [21]) but do not generate mono-HETEs or 5-1ipoxygenase products.…”
Section: Resultsmentioning
confidence: 72%
“…We recently reported that human platelets are cytotoxic to T. gondii tachyzoites, and TX release is important in this platelet-mediated toxoplasmacidal activity (21). Surface membrane vesiculation and cytoplasmic lysis in the T. gondii are prominent ultrastructural features of TXA2-induced injury (21). It is possible that TX generation by freshly isolated monocytes may contribute to the previously demonstrated (2) cytotoxic effect of these cells against T. gondii.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, this e¡ector mechanism cannot be identi¢ed in mice (Schwartzman et al 1990). Similarly, human platelets, via thromboxane production, have been shown to lyse parasitized cells (Yong et al 1991), although again a similar mechanism has not been identi¢ed in mice. However, depleting both wild-type mice and iNOSde¢cient mice of granulocytes, which have also been shown to have toxoplasmacidal activity in vitro (Wilson & Remington 1979), by using the RB6-8C5 antibody, results in signi¢cantly more rapid death in both the intraperitoneal (Scharton-Kersten et al 1997) and peroral routes of infection (P. Sayles, personal communication).…”
Section: Ot H E R P O S S I B L E E F F Ec To R M Ec H a N I Sm S C Omentioning
confidence: 99%